Mr. Garbage - Hooks, William H.; Duke, Kate (Milwaukee, Wis. : Gareth Stevens Publishing, 1997)
Five-year-old Eli's enthusiasm for saving the planet gets out of hand as he continues to fill his room with more and more junk he intends to recycle.
K-3
Keywords: Environmental protection -- Fiction; Recycling (Waste, etc.) -- Fiction